PROTÓTIPO DE UM FOGÃO À LENHA COMO ALTERNATIVA AOS MODELOS TRADICIONAIS MENOS EFICIENTES - Almeida, Milena Maria Van Der Neut de (2017)
In this research, an improved cookstove was constructed to have a lower consumption of firewood and less potential exposure to carbon monoxide than the traditional cookstove. Eight species of Eucalyptus spp. and Corymbia citriodora was used as fuel. The improved cookstove presented 13% efficiency, 0.7 kg/h wood consumption and 0.4 kW calorific power; while the traditional cookstove had 0.9% energy efficiency, 2.6 kg/h wood consumption and 0.1 kW calorific power. Due to better aeration of the cellular cavities in firewoods of higher porosity, 2.8 kg/h in the consumption of firewood increases for each variation of one unit in the porosity and; therefore, a better burning of the fuel occurs. The energy content of firewood, expressed by the Higher Heating Value (HHV), was predicted by the chemical and proximate composition. The chemical composition had an influence in the regression equation coefficient of 48% of lignin, 28% of extractives and 25% of holocellulose. Additionally, about proximate composition, as lignin is the main responsible for the formation of fixed carbon and holocellulose for the volatile matter, it is observed a participation on the HHV estimate of 56% fixed carbon and 45% volatile matter. Referring to the potential exposure of carbon monoxide by the cookstove user, the improved and traditional stove had 62% and 550% respectively higher potential than the World Health Organization (WHO) standard that allows 40 h-mg/m³. In conclusion, the improved stove is more efficient and powerful than the traditional cookstove, also consumes less firewood in its operation and promotes a lower release of carbon monoxide.